'Eye is a window to the pulse': bilateral ocular ischaemic syndrome as a presenting manifestation of Takayasu arteritis. (29th April 2013) - Shailaja, S; Vivek, G; Shetty, Ranjan; Kamath, Yogish
Abstract : A 22-year-old lady presented with gradually progressive visual loss and chronic pain in both the eyes of 3 months duration. The clinical examination and fundus fluorescein angiography were suggestive of bilateral ocular ischaemic syndrome. Her upper limb pulses were feeble and blood pressure was not recordable in the same. Carotid Doppler revealed a bilateral carotid artery occlusion. Systemic markers for inflammation were elevated. Diagnosis of Takayasu arteritis was made on the basis of clinical and laboratory findings. Takayasu arteritis should be considered in the differential diagnosis of ocular ischaemic syndrome, particularly in young Asian women.